2017
DOI: 10.3847/1538-4357/836/2/168
|View full text |Cite
|
Sign up to set email alerts
|

A Chemical Composition Survey of the Iron-complex Globular Cluster NGC 6273 (M19)*

Abstract: Recent observations have shown that a growing number of the most massive Galactic globular clusters contain multiple populations of stars with different [Fe/H] and neutron-capture element abundances. NGC 6273 has only recently been recognized as a member of this "iron-complex" cluster class, and we provide here a chemical and kinematic analysis of >300 red giant branch and asymptotic giant branch member stars using high-resolution spectra obtained with the

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
55
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 52 publications
(57 citation statements)
references
References 210 publications
2
55
0
Order By: Relevance
“…Our previous studies, however, found a significant CN-CH positive correlation, instead of an anticorrelation, among RGB stars in M22 and NGC 6273 Lim et al 2015). Interestingly, both GCs are known to host multiple stellar populations with different heavy element abundances (see also Marino et al 2011;Johnson et al 2017). Since NGC 5286 is also one of the GCs showing spreads in the abundances of heavy elements, we would expect a similar positive correlation between CN and CH indices.…”
Section: The Cn-ch Positive Correlation In Globular Clusters With Heamentioning
confidence: 86%
“…Our previous studies, however, found a significant CN-CH positive correlation, instead of an anticorrelation, among RGB stars in M22 and NGC 6273 Lim et al 2015). Interestingly, both GCs are known to host multiple stellar populations with different heavy element abundances (see also Marino et al 2011;Johnson et al 2017). Since NGC 5286 is also one of the GCs showing spreads in the abundances of heavy elements, we would expect a similar positive correlation between CN and CH indices.…”
Section: The Cn-ch Positive Correlation In Globular Clusters With Heamentioning
confidence: 86%
“…ChMs have also revealed the presence of two classes of clusters, namely Type I and Type II GCs, with the latter constituting ∼17% of the objects and displaying a more complex chemical pattern, including variations in Fe and heavy elements (e.g. Marino et al 2009Marino et al , 2015Yong & Grundahl 2008;Yong et al 2014;Johnson et al 2015Johnson et al , 2017Da Costa et al 2009). According to some scenarios, GCs have experienced multiple bursts of star formation where 2G stars formed from material polluted by more massive 1G stars (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…As noted by numerous previous authors (e.g., Armandroff & Da Costa 1991;Olszewski et al 1991;Idiart et al 1997;Rutledge et al 1997;Battaglia et al 2008), the near-infrared CaT lines are reliable tracers of a star's metallicity and are relatively insensitive to age and [Ca/Fe] abundance variations (e.g., Cole et al 2004;Carrera et al 2007;Da Costa 2016b). Following the methods outlined in Yong et al (2016) and Johnson et al (2017a), we employed the calibration described in Mauro et al (2014) to convert the measured CaT EWs into [Fe/H] abundances. A key advantage of the Mauro et al (2014) CaT-[Fe/H] calibration is that a star's luminosity parameter is defined as the difference between its K S -band magnitude and that of the HB.…”
Section: Calcium Triplet [Fe/h] Determinationsmentioning
confidence: 99%
“…These "iron-complex" clusters exhibit significant [Fe/H] dispersions and share a common trait that metallicity and s-process enhancements are strongly correlated (e.g., Norris & Da Costa 1995;Smith et al 2000;Johnson & Pilachowski 2010;Marino et al 2011aMarino et al , 2011bYong et al 2014;Johnson et al 2015bJohnson et al , 2017aMarino et al 2015;Da Costa 2016a). 9 Since second-peak s-process elements are thought to be produced during the late-stage evolution of low-and intermediate-mass AGB stars (e.g., Busso et al 1999), the correlation between [Ba, La/Fe] and [Fe/H] is consistent with the idea that ironcomplex clusters experienced prolonged star formation and chemical enrichment compared to monometallic systems.…”
Section: Introductionmentioning
confidence: 99%